Incidence of malignancy in gastric/antral perforation - Bhaskar, Sumit; Kumari, Priyanka; ., Sweta; Sinha, Dipendra K. (International Surgery Journal, 2019)
Background: Gastrointestinal perforation is one of the most commonly encountered cases in emergency department. Acute perforation of the stomach and duodenum causes significant morbidity and mortality. These perforations occur more commonly as a complication of peptic ulcer disease but in a few cases gastric cancer also present as gastric/antral perforation. Previously it was reported that approximately 10-16% of all gastric are caused by malignancy/gastric cancer. To study the incidence of malignancy in gastric perforation in present time, a study was carried out at our institute including all cases of gastric/antral perforations that presented to emergency department over a period of two years. Methods: Cases of gastric/antral perforation that presented to our emergency were included in study. Biopsy from the margin of perforation was taken and sent for histopathological examination. Results obtained were further analysed with respect to total no. of cases, age, sex, personal habits and histopathological type. Results: Out of total 60 cases that were included in study, biopsy report of 5 cases came to positive of malignancy. Conclusions: The incidence of malignancy in gastric/antral perforation was found to be 8% in our study which shows a decline in this region as compared to incidence in the world.